2016
DOI: 10.2298/tsci140313114a
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis of MHD flow due to unsteady bi-directional stretching sheet through porous space

Abstract: In this article unsteady 3-D MHD boundary layer flow and heat transfer analysis with constant temperature and constant heat flux in a porous medium is considered. The boundary layer flow is governed by a bi-directional stretching sheet. Similarity transformations are used to transform the governing non-linear partial differential equations to ordinary differential equations. Analytical solutions are constructed using homotopy analysis method. Convergence analysis is also presented through tabular data. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The power indices r and s decided how the temperature or the heat flux at the sheet varies in the , -plane. The stretching phenomenon in this direction has already studied by various authors Liu and Andersson (2008), Ahmad et al (2011), Ahmad et al (2014).…”
Section: Mathematical Formulationmentioning
confidence: 93%
See 2 more Smart Citations
“…The power indices r and s decided how the temperature or the heat flux at the sheet varies in the , -plane. The stretching phenomenon in this direction has already studied by various authors Liu and Andersson (2008), Ahmad et al (2011), Ahmad et al (2014).…”
Section: Mathematical Formulationmentioning
confidence: 93%
“…Following Awais et al (2014) and Ahmad et al (2014), we introduce the following dimensionless variables…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Recently researchers have also exploited the effect of hybrid nanofluids over the stretching sheet to enhance the heat transfer. 3339 Acharaya and Mabood 40 worked on the radiative Fe 3 O 4 -graphene hybrid nanofluid flow over permeable bended structure and found that hybrid nanofluid exhibits larger velocity than conventional nanofluid. The revolving hybrid nanosuspension flow (Alumina-copper nanoparticle with water as base fluid) in microchannel within solar unit has been studied by Acharaya.…”
Section: Introductionmentioning
confidence: 99%
“…Such investigations were also carried out by Awais et al [38] and obtained analytical solutions. Recently, Ahmad et al [39] address the unsteady magnetohydrodynamic flow with heat transfer through porous space of a viscous fluid due to stretching sheet. Later, same phenomenon was used by Ahmad et al [40,41] for non-Newtonian Maxwell and Oldroyd-B fluid.…”
Section: Introductionmentioning
confidence: 99%